Pediatric M5 acute myeloid leukemia with MLL-SEPT6 fusion and a favorable outcome. (2021) - Chebly, Alain; Djambas Khayat, Claudia; Yammine, Tony; Korban, Rima; Semaan, Warde; Bou Zeid, Jessica; Farra, Chantal
Abstract: Acute myeloid leukemia (AML) patients with MLL-SEPT6 fusion represent a small subset of AML. The uncommon MLL-SEPT6 rearrangement results from t(X;11) or other variants like ins(X;11), and it is usually associated with complex cytogenetic abnormalities. We herein report a case of AML-M5-infant with ins(X;11)(q24;q23q13) and MLL-SEPT6 . The one-year-old boy presented with leukocytosis, anemia and thrombocytopenia. He had a favorable response to chemotherapy according to ELAM02protocol and is currently in complete remission. We here, highlight the occurrence of MLL-SEPT6 as the sole abnormality in a pediatric-AML-M5 case, discuss the prognostic implication of this genetic variant, while reviewing previously reported AML- MLL-SEPT6 cases.